2017
DOI: 10.18632/oncotarget.23732
|View full text |Cite
|
Sign up to set email alerts
|

The hypoxia-responsive lncRNANDRG-OT1promotes NDRG1 degradation via ubiquitin-mediated proteolysis in breast cancer cells

Abstract: Hypoxia can lead to solid tumor aggressiveness by driving multiple signaling pathways. Long non-coding RNAs respond to several extrinsic stimuli, causing changes in cancer cells by participating in multiple steps of gene expression. However, genomic profiling of long non-coding RNAs regulated by oxygen in breast cancer remained unclear. Therefore, the aims of this study were to identify oxygen-responsive long non-coding RNAs in breast cancer cells, and to delineate their regulatory mechanisms. The expression p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 37 publications
1
35
0
Order By: Relevance
“…Furthermore, miRNAs are capable of regulating the occurrence and development of the nervous system, and some specific miRNAs can regulate the pathophysiological processes of neurological diseases. For example, miR‐183 has been reported to share a close association with the occurrence of glioma, miRNA‐129‐2‐3p and miRNA‐935 are expressed in plasma and brain tissues of intractable epilepsy, and miR‐323a‐5p is abnormally expressed in patients with refractory epilepsy caused by focal cortical dysplasia …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, miRNAs are capable of regulating the occurrence and development of the nervous system, and some specific miRNAs can regulate the pathophysiological processes of neurological diseases. For example, miR‐183 has been reported to share a close association with the occurrence of glioma, miRNA‐129‐2‐3p and miRNA‐935 are expressed in plasma and brain tissues of intractable epilepsy, and miR‐323a‐5p is abnormally expressed in patients with refractory epilepsy caused by focal cortical dysplasia …”
Section: Discussionmentioning
confidence: 99%
“…For example, miR-183 has been reported to share a close association with the occurrence of glioma, miRNA-129-2-3p and miRNA-935 are expressed in plasma and brain tissues of intractable epilepsy, and miR-323a-5p is abnormally expressed in patients with refractory epilepsy caused by focal cortical dysplasia. [28][29][30][31] Evidence has been provided that miR-135a-5p can inhibit tumor cell proliferation and promote the apoptosis of tumor cells in many tumors, while its role in epilepsy has yet to be adequately identified. 32 Reports have suggested that miR-135a-5p confer neuronal protection in mice with Alzheimer's disease by regulating potassium channels.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA NDRG1-OT1 was found to be significantly upregulated in hypoxia and inhibited the expression of NDRG1 in several breast cancer cell lines [33]. Here, we further discovered that although the overall effect of NDRG1-OT1 on NDRG1 was inhibitory, different fragments of NDRG1-OT1 played various roles in regulating the target gene via recruiting different proteins.…”
Section: Discussionmentioning
confidence: 65%
“…In recent research in our laboratory, we first renamed the lncRNA lnc-NDRG1-1 as NDRG1-OT1 (NDRG1 overlapping transcript 1) according to the guidelines for non-coding RNA nomenclature [32]. NDRG1-OT1 was induced under hypoxia in breast cancer cells [33], but its function remained unclear. We discovered that ectopic expression of NDRG1-OT1 could inhibit NDRG1 expression at both RNA and protein levels [33].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation